Effects of temperature and mobility on COVID-19 incidence (Journal of Statistics on Health Decision, 2022)
Background/Objective: The purpose of this study was to evaluate the association between COVID-19 weekly case numbers with the trend, average temperature (AT) and mobility (MOB) at the national level and by regions, in Portugal.Methods: We compiled a weekly dataset including COVID-19 case numbers, average temperature and mobility during the period of March 23, 2020, to August 30, 2022. Negative binomial regression was fitted to estimate the effect of covariates on the COVID-19 case numbers.Results: We observed a significant increasing effect over time in most regions, negative temperature effect, in all regions, and a positive mobility effect, in most regions, on the number of cases using a two-week lag.Conclusion: Increased mobility and low temperatures were associated with higher numbers of cases of COVID-19 infection.